Taxonomic revision of Richardiodes Hendel (Diptera, Richardiidae) - Wendt, Lisiane Dilli; Ale-Rocha, Rosaly (Zootaxa, 2016)
Richardiodes Hendel is a genus scarcely known taxonomically and two species are recognized: Richardiodes rectinervis Hendel from Brazilian Amazon and R. trimaculata Hennig from Peru. Herein, these two species are revised and illustrated. Examination of non-type specimens revealed considerable variation in the general body color, and the geographic distribution of each species has been expanded, especially of R. rectinervis. The limits of the genus are revised and better supported with the addition of new diagnostic characters. The male and female terminalia are described and illustrated for the first time.